Renewable energy consumption and health outcomes: Evidence from global panel data analysis - Muhammad Tariq Majeed; Tania Luni; Gulreen Zaka (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2021)
Energy consumption is an essential part of our daily lives and is considered the backbone of economic development and human welfare. It is widely admitted that energy security ensures access to health, higher efficiency, education, and economic growth. Energy consumption has a profound impact on human health depending on the source used for energy generation. The current study investigates the link between renewable energy and human health for 155 economies by employing panel techniques including pooled ordinary least squares, random effects, fixed effects, two-stage least squares, and generalized method of moments. Empirical findings support improved health from using renewable energy. Renewable energy increases life expectancy and decreases the mortality rate. The positive relationship between clean energy and human health suggests that clean energy helps to control chronic diseases thus leading to high life expectancy, low mortality, and fewer incidence of tuberculosis. It is further concluded that economic growth, trade, and urbanization also produce better health outcomes. The sensitivity analysis also endorses the robustness of the results. Therefore, countries should promote the use of renewable energy which not only improves health outcomes but also helps in achieving climate goals. This study is novel as previous studies ignored the empirical impact of renewable energy on health outcomes.
Keywords: 330; renewable energy consumption; fossil fuel consumption; solid fuelsconsumption; life expectancy; mortality rate; tuberculosis; urbanization